The Influence of Servant Leadership on Organizational Citizenship Behavior with The Mediation of Emotional Intelligence - Ismira, Shafiya Nilam; Andriani, Chichi (Human Resource Management Studies, 2023)
The purpose of this study was to analyze : (1) The influence of servant leadership on organizational citizenship behavior at PT. Telkom Access Padang. (2) The influence of servant leadership on emotional intelligence in employees of PT. Telkom Access Padang. (3) The influence of emotional intelligence on the behavior of emplyees of the organization at PT. Telkom Access Padang. (4) The effect of servant leadership on organizational citizenship behavior at PT. Telkom Access Padang through emotional intelligence. The population in this study were all employees of PT Telkom Access Padang, totaling 148 people. While the number of samples in this study were 60 people by using the sampling technique is proporsional clustered simple random sampling. The analysis technique used is SEM analysis using SmartPLS 4. The results of the study show that: (1) Servant leadership has a positive and significant effect on organizational citizen behavior at PT. Telkom Access Padang. (2) Servant leadership has a positive and significant effect on emotional intelligence in employees of PT. Telkom Access Padang. (3) Emotional intelligence has a positive and significant effect on the behavior of organizational members at PT. Telkom Access Padang. (4) Servant leadership has a positive and significant effect on the behavior of organizational members with emotional intelligence as a mediating variable for employees of PT. Telkom Access Padang.